Commonfund ESG - Elias, Jaan, (SAGE knowledge. Cases., 2016)
ESG (Environmental Social and Governance) investing had become an increasingly hot topic in the financial community. Could Commonfund offer its endowment clients some investment vehicle that would satisfy ESG concerns while producing sufficient returns?